Effects of Clostridium butyricum and a Bacteriophage Cocktail on Growth Performance, Serum Biochemistry, Digestive Enzyme Activities, Intestinal Morphology, Immune Responses, and the Intestinal Microbiota in Rabbits - Pan Huang; Xuemei Cui; Zhipeng Wang; Chenwen Xiao; Quanan Ji; Qiang Wei; Yee Huang; Guolian Bao; Yan Liu (Antibiotics, 2021)
The objective of this study was to assess the effects of dietary supplementation with Clostridium butyricum (CB) and a bacteriophage cocktail (BP) on growth performance, serum biochemical parameters, intestinal digestive and oxidase enzymes, intestinal morphology, immune responses, and the cecum microbiota in rabbits. In total, 108 New Zealand rabbits (5 weeks old) were randomly and equally allotted into three dietary treatment groups (four replicates per treatment, n = 36/treatment): (1) the control (CN) group—rabbits fed the basal diet; (2) CB group—rabbits fed the basal diet supplemented with 100 mg/kg diet Clostridium butyricum; and (3) BP group—rabbits fed the basal diet supplemented with 200 mg/kg diet BP cocktail, respectively, for 6 weeks. Compared with the CN diet, dietary CB and BP inclusion increased the average daily gain (ADG) and average daily feed intake (ADFI) and decreased the feed/gain (F/G) ratio of rabbits. Furthermore, CB increased the digestive enzyme activity (α-amylase and trypsin in the ileum); the chymotrypsin activity was also significantly increased in the duodenum and jejunum. Supplementation with CB significantly enhanced antioxidant capacity (SOD and GSH-Px) in the jejunum and ileum and reduced MDA levels. Additionally, rabbits fed CB had significantly elevated villus height (V) and (V/C) ratios but reduced crypt depth (C). Moreover, dietary CB supplementation markedly increased the ileal expression of tight junction proteins (occludin, ZO-1, and claudin-1) and increased secretory immunoglobulin A (sIgA) production. High-throughput sequencing indicated that the microbiota in the rabbit intestine was altered by CB and BP. Venn diagrams and heatmap plots revealed that the gut microbial community composition varied obviously among rabbits fed different diets. Specifically, CB increased the relative abundance of beneficial bacteria to maintain intestinal barrier homeostasis, whereas BP decreased the relative abundance of Gammaproteobacteria, which included a plenty of pathogenic bacteria.